Mengatasi Konversi Beragama pada Remaja: Pembelajaran dengan Memanfaatkan Konsep Zone of Proximal Development di Pesantren Al-Ihya Ulumaddin - Toifur Toifur (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: This paper reveals the existence of religious conversion among adolescent. This condition must be realized immediately because many people see this as a natural symtoms. In Fact, religious conversion among teenagers occur due to changes in â€œvalue systemsâ€ due to the structural pattern of development of science and technology, which is not filtered properly. Impact, many teenagers who can not manage themselves so that doubting the existence of religion as the truth. Therefore, the religious attitude of adolescents are affected by rationalization of the surroundung environment. Joints noble religion was fading. In this paper, the zone proximal development is the right direction for young people to have a religious spirit. Keywords: Religion, Youth, Conversion, Proximal, and Learning.